Analysis of the Impact of Negotiations in Resolving Team Conflicts in Hospitality Organizations - Ni Putu Linda Dian Lestari; I Gede Bayu Wijaya (Universitas KH. Abdul Chalim Mojokerto, 2025)
Conflict in work teams is a common phenomenon in hospitality organizations that have dynamic and multicultural work characteristics. This study aims to analyze the impact of implementing negotiation strategies in resolving team conflicts in hospitality organizations. The research method used is a qualitative study with a literature study approach. The results of the study indicate that negotiation as a form of conflict management has a positive impact in reducing conflict escalation, improving communication between team members, and increasing work effectiveness. The context of cultural diversity, leadership style, and emotional intelligence are important factors in the success of the negotiation process. These findings emphasize the importance of negotiation training and strengthening soft skills for managers and hotel staff to create a harmonious work environment.